ANALYZING STUDENT MOTIVATIONS FOR SELECTING PGMI AS THEIR MAJOR - Darmiah, Darmiah; Marvida, Tria (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2024)
This study examines the motivations behind students’ choices to pursue a major in Primary Islamic Education Teacher Training (PGMI) at the Faculty of Tarbiyah and Teacher Training, UIN Ar-Raniry Banda Aceh. PGMI aims to prepare graduates with competencies in foundational Islamic education and child development, equipping them to be creative, productive, and independent educators. Given the varied internal and external motivations influencing student decisions, understanding these motivations is essential, as they play a crucial role in academic success and career satisfaction. Accurate choice of major can significantly impact student achievement and future opportunities, while an inappropriate choice may hinder career potential. Employing a quantitative, descriptive-exploratory approach, this study seeks to answer the question,